Plant Pest Risk Analysis Concepts and Applications - Devorshak, Christina; Ebooks Corporation (Wallingford : CABI, 2012)
This text provides instruction on the concepts and application of risk analysis in the field of regulatory plant protection, covering topics such as the background on why and how risk analysis is conducted and specific methods for implementing risk analysis. This book also provides useful exercises and case studies to aid students of plant pathology and crop protection in their absorption of the subject. Equally useful for practitioners, this book is written by experts with a wealth of national and international experience. Students of plant pathology and crop protection as well as practitioners and professional courses on pest risk analysis.
Contenido: 11. Pest Risk Assessment12. Mapping, Climate and Geographic Information for Risk Analysis; PART IV: PEST RISK MANAGEMENT, RISK COMMUNICATION AND UNCERTAINTY; 13. Pest Risk Management Theory and Background; 14. Pest Risk Management Applications and Practice; 15. Risk Communication in Pest Risk Analysis; 16. Uncertainty in Pest Risk Analysis; 249
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: CONTROL DE PLAGAS EN PLANTAS; EVALUACION DE RIESGOS; PLAGAS AGRICOLAS; PROTECCION DE LAS PLANTAS